Application of GANs-based virtual environment generation in automatic driving simulation training - Wang, Haiyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
The safety and efficiency of autonomous driving technology rely heavily on precise simulation training, which is greatly limited by the quality and diversity of the training environments. Generative Adversarial Networks (GANs), as a powerful generative tool, can create highly realistic virtual images and environments, providing complex and variable training data for autonomous vehicles, thus enhancing the algorithms’ generalization ability and adaptability. This study first reviews the major challenges faced by autonomous driving technology and the shortcomings of current simulation training methods, such as the monotony of existing training data and lack of scenario variation.Further, this paper provides a detailed introduction to the working mechanism of GANs, including the interaction process between its core components—the generator and the discriminator. Through case analysis, this paper demonstrates how GANs effectively generate new training scenarios without actual data, and these scenarios closely align with the real world in visual and physical properties. Particularly in simulating complex traffic scenes, different weather conditions, and various emergency events, GANs showcase their powerful capabilities.Additionally, this paper explores the practical operations involved in integrating GAN-generated virtual environments into the autonomous driving simulation training framework, including the technical details of data integration and the requirements for adjusting training algorithms. Through several specific application cases, this paper validates the effectiveness of GAN-enhanced simulation training in improving the performance of autonomous driving algorithms.Despite the great potential of GANs in autonomous driving training, there are still some challenges in practical applications, including the validation of the realism of generated data, high computational resource demands, and potential ethical issues. The article concludes by discussing possible strategies to address these challenges and anticipates future directions in technology development, such as improving the stability and efficiency of GAN algorithms and developing new evaluation standards to ensure the reliability and effectiveness of generated environments.